Enhanced Microstructural and Mechanical Properties of Mig Welded Al 7075 Alloy Under Longitudinal Vibrations - Machedon-Pisu Mihai; Machedon-Pisu Teodor (MDPI, 2025)
In many areas such as the automotive, aircraft, and building industries, the high-strength aluminum alloy Al 7075 is frequently used due to its appropriate properties as a lightweight structural material. However, due to modest weldability, it is challenging to obtain high-quality welds with suitable mechanical properties, as cracks are generated while welding. Moreover, in order to avoid post-welding heat treatments and the use of complex welding equipment, in this paper the Al 7075 alloy is welded with MIG under longitudinal vibrations by using the Al 4043 alloy as filler material. As a consequence of strengthening the HAZ through precipitation, the mechanical and structural properties of the welded joints can be improved. These are investigated both under longitudinal forced vibrations at 50 Hz and without such vibrations. The results reveal improvements in terms of reducing the risk of hot cracking, obtaining a band structure free of porosity of the welds, improving the hardness of the welds under vibrations by 8.7% to 12.5%, and improving the tensile strength of the plates welded under vibrations by 12 to 15.5% in comparison to no vibrations. In relation to other welding procedures, the proposed procedure is more cost-effective and the weld quality is improved during the welding process.